A method for preparing semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen

The preparation of K and Al-SrTiO3 semiconductor composite hydrogel catalysts by solid phase grinding and chemical crosslinking methods has solved the problems of low efficiency and high process cost of the existing solar photocatalytic water decomposition reaction system, and achieved efficient and stable photocatalytic water decomposition effect.

CN119281403BActive Publication Date: 2025-04-25扬州市常发新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411830561.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-25
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The conversion efficiency of the existing solar photocatalytic water decomposition reaction system is low, and photocatalysts have problems of process difficulty and high cost in large-scale applications.

Method used

Solid phase grinding was used to prepare K and Al bimetal ions co-doped SrTiO3, and PVA/PAM sol was prepared by chemical crosslinking. Finally, doped SrTiO3 was supported on the hydrogel to form a K and Al-SrTiO3 semiconductor composite hydrogel catalyst.

Benefits of technology

It improves photocatalytic activity, reduces process difficulty and cost, enhances the stability and salt resistance of the catalyst, making it more suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281403B_ABST
    Figure CN119281403B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of new materials, and specifically proposes a method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater for hydrogen production. The preparation method comprises the following steps: uniformly mixing a dual-source compound of K and Al with SrTiO3, adding SrCl2 for solid phase sintering at a certain temperature, filtering and washing with water, and drying to obtain a target product, thereby obtaining K and Al dual metal ion co-doped SrTiO3, and supporting RhCrO x With CoOOH as a co-catalyst, the obtained photocatalyst can realize pure water decomposition. The photocatalyst has good catalytic activity; and the preparation process is simple to operate, the experimental environment is safe, the reaction conditions are mild, and the reagents used are low in price.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen. Background Art

[0002] At present, there have been decades of research on solar photocatalytic water splitting reaction systems. Although a certain degree of progress has been made, the overall solar hydrogen production efficiency is still very low (less than 1%), and there is still a big gap from the demand for industrialization. People are committed to improving the intrinsic activity of photocatalysts through various methods, including morphology control, element doping, heterojunction construction and defect engineering. Among common semiconductors, strontium titanate (SrTiO3), as a perovskite oxide, has high catalytic activity, good stability, and flexible coordination of band gap and band edge. It is considered to be a good pure water splitting photocatalyst. Early research by Professor Domen's team in Japan found that the synthesis of Al-SrTiO3 by the flux method can improve the crystallinity of the material. After constructing a co-catalyst on the surface of the material, the catalytic performance is improved, and the STH conversion efficiency reaches 0.67%. However, it is worth noting that although the doping of elemental ions can reduce the energy band gap, the defect structure formed at the same time of injection will also form a recombination center for photogenerated carriers, among which Al 3+ Doping Ti 3+ The sites are occupied, resulting in charge imbalance and thus reducing the photocatalytic activity.

[0003] In addition to the intrinsic activity of photocatalysts, the large-scale application of catalysts in efficient solar hydrogen (H2) production also needs to be considered, especially the design of the photocatalytic system. For example, slurry reactors are the main form of large-scale photocatalysis, which are not ideal due to the aggregation of catalyst particles, severe light scattering and the high cost of continuous stirring. Recently, some explorations have been made in reactors with immobilized photocatalysts, including particle sheet type, thin film type and flat plate type, such as the assembly of BiVO3 / Au / SrTiO3 catalyst sheets, and the STH can be improved to 1.1%. However, these reactors still have many practical limitations, including potential reverse reactions during product separation, continuous leaching of photocatalysts, and poor mass transfer between closely packed photocatalysts. Summary of the invention

[0004] In view of this, the present invention proposes a method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen, aiming to improve the catalytic activity of the semiconductor composite hydrogel photocatalyst while reducing its process difficulty and cost, making it more suitable for large-scale industrial applications.

[0005] The technical solution of the present invention is achieved as follows: The present invention provides a method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen, which comprises the following steps:

[0006] S1. Preparation of K and Al double metal ion co-doped SrTiO3 by solid phase grinding;

[0007] S2, preparing PVA / PAM sol by chemical cross-linking method;

[0008] S3. K and Al double metal ions are co-doped into SrTiO3 by liquid phase grafting method and loaded on the upper layer of PVA / PAM double-chain network three-dimensional porous hydrogel to obtain K, Al-SrTiO3 semiconductor composite hydrogel.

[0009] In the above-mentioned embodiment, the doping of K and Al ions can regulate the band gap width of SrTiO3, reduce the recombination probability of electrons and holes, improve the separation efficiency of photogenerated electrons and holes, and thus improve the photocatalytic activity. At the same time, the use of hydrogel as a matrix can provide a three-dimensional porous structure, which is conducive to the uniform distribution and fixation of the photocatalyst, prevent particle aggregation, increase the contact area between the reactant and the catalyst, and promote the photocatalytic reaction. At the same time, the chemical crosslinking method can accurately control the crosslinking density and pore structure of the hydrogel by adjusting the type and amount of the crosslinking agent, thereby optimizing the mechanical properties and mass transfer performance of the hydrogel. Compared with the physical crosslinking method, the hydrogel structure formed by chemical crosslinking is more stable, and can maintain its structural integrity for a long time and under harsh reaction conditions, which helps to improve the salt resistance of the composite hydrogel.

[0010] In the above embodiment, in S1, the molar proportion of K in the SrTiO3 co-doped with K and Al double metal ions is 2%, and the molar proportion of Al is 2%.

[0011] In some embodiments, in S1, the method for preparing K, Al bimetallic ion co-doped SrTiO3 by solid phase grinding includes: mixing K salt and Al salt with SrTiO3, adding ethanol for sufficient wet grinding, drying, and subjecting to a first heat treatment to obtain a precursor, and then fully grinding the precursor with strontium chloride and subjecting to a second heat treatment to obtain K, Al bimetallic ion co-doped SrTiO3.

[0012] In the above implementation, solid phase grinding can not only ensure the uniform mixing of K and Al salts with SrTiO3, but also improve the uniformity of doping. At the same time, this method does not require complex equipment, is simple to operate, and is suitable for large-scale production. Through two-step heat treatment (500°C and 900-1200°C), the doping effect and the crystallinity of the material can be gradually improved to ensure that K and Al ions are evenly distributed in the SrTiO3 lattice. The first heat treatment temperature is relatively low, which helps to avoid adverse chemical reactions that may occur at high temperatures.

[0013] In some embodiments, the first heat treatment temperature is 500° C. and the time is 10 h.

[0014] In some embodiments, the second heat treatment is performed at a temperature of 900-1200° C. for a time of 10-20 h.

[0015] In some embodiments, after the second heat treatment, the method further includes dissolving the sample and filtering it to obtain K and Al bimetallic ion co-doped SrTiO3.

[0016] In some embodiments, after obtaining K and Al bimetallic ion co-doped SrTiO3, the method further comprises mixing K and Al bimetallic ion co-doped SrTiO3 with NaRhCl6, Cr(NO3)2 and Co(NO3)3 to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0017] In the above embodiment, Rh, Cr, and Co elements are introduced to form RhCrO x The synergistic effect of different metal oxides can promote the separation of photogenerated electrons and holes, further improving the photocatalytic performance of the catalyst. Multi-metal doping and composite nanostructures help improve the chemical stability and mechanical strength of the catalyst and extend its service life.

[0018] In some embodiments, RhCrO x / K, in the Al-SrTiO3 / CoOOH nanocomposite photocatalyst, the loading amount of Rh is 0.1wt%, the loading amount of Cr is 0.05wt%, and the loading amount of Co is 0.05wt%.

[0019] In some embodiments, in S2, the step of preparing the PVA / PAM sol by chemical crosslinking method includes: mixing the PVA solution with the AM monomer solution, adding an auxiliary agent, and curing for 0.5-1h to obtain the PVA / PAM sol.

[0020] In some embodiments, the mass ratio of PVA to AM monomer is 1:(0.5-2).

[0021] In some embodiments, the PVA solution is an aqueous solution of polyvinyl alcohol, the AM monomer solution is an aqueous solution containing acrylamide monomer and N,N'-methylenebisacrylamide, and / or; the auxiliary agent includes ammonium persulfate, glutaraldehyde and concentrated hydrochloric acid, and / or; the curing temperature is 50°C.

[0022] In the above implementation, by adjusting the ratio of PVA to AM monomers, and the amount of cross-linking agent and initiator, the cross-linking density of the PVA / PAM sol can be precisely controlled, thereby adjusting its mechanical properties and pore structure. Compared with the physical cross-linking method, the chemical cross-linking method forms a more stable network structure and can maintain good structural integrity in a complex reaction environment. By adjusting the curing time and temperature, the curing speed and degree of the sol can be precisely controlled to meet different application requirements.

[0023] In some embodiments, the amount of N,N'-methylenebisacrylamide used is 1-2 wt % of the acrylamide monomer.

[0024] In some embodiments, the amount of ammonium persulfate used is 0.5-2 wt % of the AM monomer.

[0025] In some embodiments, the amount of concentrated hydrochloric acid used is 10-100 μL of concentrated hydrochloric acid added to every 10 ml of PVA solution.

[0026] In some embodiments, in S3, the preparation method of the K, Al-SrTiO3 semiconductor composite hydrogel includes: dispersing the K, Al bimetallic ions co-doped SrTiO3 obtained in S1 in water to obtain a K, Al-SrTiO3 suspension, dropping the K, Al-SrTiO3 suspension on the PVA / PAM sol prepared in S2, freezing it, curing it at 80°C for 1-5h, and then freeze-drying it at -20°C for 24-60h to obtain a K, Al-SrTiO3 semiconductor composite hydrogel.

[0027] In some embodiments, the thickness of the catalyst layer in the K, Al-SrTiO3 semiconductor composite hydrogel prepared above is 0.1-0.5 cm.

[0028] In a second aspect, the present invention also provides a semiconductor composite hydrogel catalyst for producing hydrogen by photolysis of seawater prepared by the above preparation method.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The invention provides a strontium titanate semiconductor composite hydrogel catalyst for solar seawater decomposition. The catalyst is a K and Al metal ion co-doped SrTiO3 composite hydrogel catalyst. Compared with pure SrTiO3 material, ion doping reduces the recombination center of photogenerated electrons and holes, and improves the photocatalytic activity of SrTiO3. The introduction of a hydrogel matrix can prevent the catalyst from agglomerating, increase the stability of the catalyst, and reduce the reaction energy barrier of water molecules on the catalyst surface. The K, Al-SrTiO3@PVA / PAM hydrogel material prepared by the invention can realize overall water decomposition in a seawater system, and has good catalytic activity and stability. In addition, the preparation process of the invention is simple to operate, the reaction conditions are mild, and the reagents used are low in price. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 The scanning electron microscope image of the K and Al-SrTiO3 catalysts prepared in Example 1 of the present invention;

[0033] Figure 2 This is a scanning electron microscope image of the PVA / PAM hydrogel prepared in Example 1 of the present invention;

[0034] Figure 3 This is a scanning electron microscope image of the K, Al-SrTiO3@PVA / PAM hydrogel prepared in Example 2 of the present invention;

[0035] Figure 4 The pure water decomposition activity diagram of K and Al-SrTiO3@PVA / PAM hydrogels prepared in various embodiments of the present invention;

[0036] Figure 5 This is a test diagram of the salt resistance of K and Al-SrTiO3@PVA / PAM composite hydrogel in Example 2 of the present invention;

[0037] Figure 6 This is the pure water decomposition activity diagram of K and Al-SrTiO3 catalysts in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0040] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0041] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0042] Studies have shown that in Sr 2+ The introduction of trace cationic metals (K + ) can stabilize the SrTiO3 structure and form a shallow defect structure, which is beneficial to improving the photocatalytic activity and stability.

[0043] Using hydrogel as a macroporous matrix to immobilize photocatalysts can prevent catalyst leaching, increase catalyst loading capacity, and improve mass transfer. Compared with systems using tightly packed photocatalyst membranes, photocatalysts embedded in hydrogels have the potential to improve photocatalytic efficiency. In addition, the hydrogel matrix has high water content, high light transmittance, and can confine nanoparticles through molecular network space, ensuring the universality of hydrogel nanocomposites and various photocatalytic fillers. On the other hand, there are still huge challenges in the study of the activity of reactant water molecules in the reaction, mainly due to the high thermodynamic stability of water molecules, which makes it difficult for H-OH bonds to dissociate. Hydrogen-bonded water molecules in hydrogels exist in the form of small clusters, and their H-OH bond breaking energy is smaller. These weakly hydrogen-bonded water molecules are more conducive to participating in the reaction on the catalyst surface after activation, thereby promoting the photocatalytic process, and their unique polymer network can complete the solar desalination process. It has been reported that water molecules in hydrogels exist in the form of small clusters, and the hydrogen bond network is easily destroyed, making it more conducive for water molecules to participate in the reaction on the catalyst surface after activation, thereby promoting the photocatalytic process. In order to expand the application scope of photocatalysis, K and Al-SrTiO3 prepared by solid phase grinding were loaded on hydrogel to realize a highly active photocatalytic system for solar seawater decomposition.

[0044] Example 1

[0045] A strontium titanate semiconductor composite hydrogel catalyst for solar seawater decomposition comprises the following steps:

[0046] First, weigh 0.008 mol of potassium carbonate, 0.008 mol of aluminum oxide and 1 g of SrTiO3, add 2 ml of ethanol, mix and grind in an agate mortar at room temperature for 1 hour, place the ground mixture in a muffle furnace, and keep it at 500°C for 10 hours. After taking it out, mix and grind it with 14 g of strontium chloride in an agate mortar for 1 hour, place the ground mixture in a muffle furnace, and keep it at 1150°C for 15 hours. After taking it out, filter and wash it with deionized water, and then place the material in a drying oven at 80°C overnight to obtain K, Al-SrTiO3 nanocatalyst material, take 0.5 g of K, Al-SrTiO3 nanoparticles and disperse them in an aqueous solution, add 1.65 mg of NaRhCl6, 0.85 mg of Cr(NO3)2 and 1.04 mg of Co(NO3)3, irradiate it with 300W xenon lamp for 1 hour, filter, wash and dry it to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0047] Secondly, 0.98g acrylamide monomer (AM), 19.6mg N, N'-methylenebisacrylamide and 10ml deionized water were mixed to obtain AM solution. Then, 1.05g polyvinyl alcohol (PVA) was dissolved in 10ml deionized water by heating and continuous stirring. 5ml PVA solution was added to the prepared AM solution, ultrasonicated in a cell disruptor for 15min, and then 0.0098g ammonium persulfate, 125μL glutaraldehyde and 40μL concentrated hydrochloric acid were added and ultrasonicated for 5min to obtain a mixed solution of AM and PVA. The solution was poured into an acrylic mold, and after degassing in a vacuum, it was placed in an oven at 50°C for pre-curing for 0.5h to obtain a sol-like PVA / PAM.

[0048] Finally, 2 mg RhCrO x / K,Al-SrTiO3 / CoOOH were dispersed in 2 ml of aqueous solution, dropped on the surface of sol-like PVA / PAM, then frozen with liquid nitrogen, put into a vacuum drying oven for curing at 80 °C for 3 h, frozen again with liquid nitrogen, put into a freeze dryer for freeze drying at -20 °C for 24 h to obtain K,Al-SrTiO3@PVA / PAM hydrogel.

[0049] The SEM image of the K, Al-SrTiO3 nanocatalyst material prepared in Example 1 is as follows: Figure 1 As shown in Figure 2, its crystal form maintains the same cubic perovskite type as SrTiO3, indicating that a small amount of metal ion doping has little effect on its crystal form change. Figure 2 As shown in Figure 2, after cross-linking, a three-dimensional porous network structure was formed, which was conducive to the embedding of photocatalytic nanoparticles. When the salt resistance test was carried out, the mass change rate reached 1.64 kg·m -2 ·h -1 The hydrogen evolution rate of Example 1 was the highest, reaching 118.9 mmol·m -2 ·h -1 The oxygen evolution rate reached 49.7mmol·m -2 ·h -1 .

[0050] Example 2

[0051] A strontium titanate semiconductor composite hydrogel catalyst for solar seawater decomposition comprises the following steps:

[0052] First, weigh 0.008 mol of potassium carbonate, 0.008 mol of aluminum oxide and 1 g of SrTiO3, add 2 ml of ethanol, mix and grind in an agate mortar at room temperature for 1 hour, place the ground mixture in a muffle furnace, and keep it at 500 ° C for 10 hours. After taking it out, mix and grind it with 14 g of strontium chloride in an agate mortar for 1 hour, place the ground mixture in a muffle furnace, and keep it at 1150 ° C for 15 hours. After taking it out, it is repeatedly filtered and washed with deionized water, and then the material is placed in a drying oven at 80 ° C overnight to obtain K, Al-SrTiO3 nanocatalyst material. Take 0.5 g of K, Al-SrTiO3 nanoparticles and disperse them in an aqueous solution, add 1.65 mg of NaRhCl6, 0.85 mg of Cr(NO3)2 and 1.04 mg of Co(NO3)3, and irradiate it with 300W xenon lamp for 1 hour, filter, wash and dry it to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0053] Secondly, 0.98g acrylamide monomer (AM), 14.7mg N, N'-methylenebisacrylamide and 10ml deionized water were mixed to obtain AM solution. Then, 1.05g polyvinyl alcohol (PVA) was dissolved in 10ml deionized water by heating and continuous stirring. 7ml PVA solution was added to the prepared AM solution, ultrasonicated in a cell disruptor for 15min, and then 0.0098g ammonium persulfate, 125μL glutaraldehyde and 40μL concentrated hydrochloric acid were added and ultrasonicated for 5min to obtain a mixed solution of AM and PVA. The solution was poured into an acrylic mold, and after degassing in a vacuum, it was placed in an oven at 50°C for pre-curing for 0.5h to obtain a sol-like PVA / PAM.

[0054] Finally, 5 mg RhCrO x / K,Al-SrTiO3 / CoOOH were dispersed in 2 ml of aqueous solution, dropped on the surface of sol-like PVA / PAM, then frozen with liquid nitrogen, put into a vacuum drying oven for curing at 80 °C for 3 h, frozen with liquid nitrogen again, put into a freeze dryer for freeze drying at -20 °C for 40 h, and K,Al-SrTiO3@PVA / PAM hydrogel was obtained.

[0055] The scanning electron microscopy image of K, Al-SrTiO3@PVA / PAM hydrogel prepared by the above method is shown in Figure 3 As shown in Figure 2, K, Al-SrTiO3 nanoparticles are embedded on the surface of the hydrogel and in some pores to prevent agglomeration during the catalytic process. When the salt tolerance test was performed, the mass change rate reached 1.61 kg·m -2 ·h -1 The hydrogen evolution rate in Example 2 was the highest, reaching 220.2 mmol·m -2 ·h-1 , the oxygen evolution rate reached 134.5mmol·m -2 ·h -1 .

[0056] Example 3

[0057] A strontium titanate semiconductor composite hydrogel catalyst for solar seawater decomposition comprises the following steps:

[0058] First, weigh 0.008 mol of potassium carbonate, 0.008 mol of aluminum oxide and 1 g of SrTiO3, add 2 ml of ethanol, mix and grind in an agate mortar at room temperature for 1 hour, place the ground mixture in a muffle furnace, and keep it at 500 ° C for 10 hours. After taking it out, mix and grind it with 14 g of strontium chloride in an agate mortar for 1 hour, place the ground mixture in a muffle furnace, and keep it at 1150 ° C for 15 hours. After taking it out, filter and wash it repeatedly with deionized water, and then place the material in a drying oven at 80 ° C overnight to obtain K, Al-SrTiO3 nanocatalyst material, take 0.5 g of K, Al-SrTiO3 nanoparticles and disperse them in aqueous solution, add 1.65 mg of NaRhCl6, 0.85 mg of Cr(NO3)2 and 1.04 mg of Co(NO3)3, irradiate with 300W xenon light for 1 hour, filter, wash and dry, and obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0059] Secondly, 0.98g acrylamide monomer (AM), 9.8mg N, N'-methylenebisacrylamide and 10ml deionized water were mixed to obtain AM solution. Then, 1.05g polyvinyl alcohol (PVA) was dissolved in 10ml deionized water by heating and continuous stirring. 10ml PVA solution was added to the prepared AM solution, ultrasonicated in a cell disruptor for 15min, and then 0.0098g ammonium persulfate, 125μL glutaraldehyde and 40μL concentrated hydrochloric acid were added and ultrasonicated for 5min to obtain a mixed solution of AM and PVA. The solution was poured into an acrylic mold, and after degassing in a vacuum, it was placed in an oven at 50°C for pre-curing for 0.5h to obtain a sol-like PVA / PAM.

[0060] Finally, 10 mgRhCrO x / K,Al-SrTiO3 / CoOOH were dispersed in 2 ml of aqueous solution, dropped on the surface of sol-like PVA / PAM, then frozen with liquid nitrogen, put into a vacuum drying oven for curing at 80 °C for 3 h, frozen again with liquid nitrogen, put into a freeze dryer for freeze drying at -20 °C for 60 h to obtain K,Al-SrTiO3@PVA / PAM hydrogel.

[0061] The K, Al-SrTiO3@PVA / PAM hydrogel prepared by the above method was applied to photocatalytic water decomposition. When the salt tolerance test was carried out, the mass change rate reached 1.67 kg·m -2 ·h -1 , the photocatalytic water splitting performance was tested in pure water under full UV-Visible spectrum irradiation, 20 ml of pure water, the light source was a 300W xenon lamp equipped with an AM1.5 filter, such as Figure 4 As shown in Figure 2, the hydrogen-oxygen ratio of the water decomposition performance of K, Al-SrTiO3@PVA / PAM hydrogel is close to 2:1, and the hydrogen evolution rate of Example 3 is 88.7 mmol·m -2 ·h -1 , the oxygen evolution rate reached 32.5mmol·m -2 ·h -1 , with good stability. And as Figure 5 As shown, K, Al-SrTiO 3 @PVA / PAM hydrogel exhibits good salt resistance.

[0062] Comparative Example 1

[0063] A strontium titanate semiconductor composite hydrogel catalyst for solar seawater decomposition comprises the following steps:

[0064] First, weigh 0.008 mol of potassium carbonate, 0.008 mol of aluminum oxide and 1 g of SrTiO3, mix and grind them in an agate mortar at room temperature for 1 hour, place the ground mixture in a ball mill, ball mill at 4000 rpm for 24 hours, and then add 1 mol of ammonium dihydrogen phosphate to continue ball milling for 1 hour. The ball-milled mixture is sieved and separated, and placed in a muffle furnace and kept at 1000°C for 8 hours. After taking it out, it is filtered and washed with deionized water, and then the material is placed in a drying oven at 80°C overnight to obtain K, Al-SrTiO3 nanocatalyst material. Take 0.5 g of K, Al-SrTiO3 nanoparticles and disperse them in an aqueous solution, add 1.65 mg of NaRhCl6, 0.85 mg of Cr(NO3)2 and 1.04 mg of Co(NO3)3, and irradiate with 300W xenon lamp for 1 hour, filter, wash and dry to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0065] Secondly, 0.98g acrylamide monomer (AM), 14.7mg N, N'-methylenebisacrylamide and 10ml deionized water were mixed to obtain AM solution. Then, 1.05g polyvinyl alcohol (PVA) was dissolved in 10ml deionized water by heating and continuous stirring. 7ml PVA solution was added to the prepared AM solution, ultrasonicated in a cell disruptor for 15min, and then 0.0098g ammonium persulfate, 125μL glutaraldehyde and 40μL concentrated hydrochloric acid were added and ultrasonicated for 5min to obtain a mixed solution of AM and PVA. The solution was poured into an acrylic mold, and after degassing in a vacuum, it was placed in an oven at 50°C for pre-curing for 0.5h to obtain a sol-like PVA / PAM.

[0066] Finally, 5 mg RhCrO x / K,Al-SrTiO3 / CoOOH were dispersed in 2 ml of aqueous solution, dropped on the surface of sol-like PVA / PAM, then frozen with liquid nitrogen, put into a vacuum drying oven for curing at 80 °C for 3 h, frozen with liquid nitrogen again, put into a freeze dryer for freeze drying at -20 °C for 40 h, and K,Al-SrTiO3@PVA / PAM hydrogel was obtained.

[0067] The salt tolerance of the K and Al-SrTiO3@PVA / PAM hydrogels prepared in the above comparative examples reached 1.68 kg·m -2 ·h -1 , which is higher than that of Example 2, and its hydrogen evolution rate is only 96.4mmol·m -2 ·h -1 , compared with 220.2mmol·m in Example 2 -2 ·h -1 Obviously low.

[0068] Comparative Example 2

[0069] A strontium titanate semiconductor composite hydrogel catalyst for solar seawater decomposition comprises the following steps:

[0070] First, weigh 0.008 mol of potassium carbonate, 0.008 mol of aluminum oxide and 1 g of SrTiO3, add 2 ml of ethanol, mix and grind in an agate mortar at room temperature for 1 hour, place the ground mixture in a muffle furnace, and keep it at 500 ° C for 10 hours. After taking it out, mix and grind it with 14 g of strontium chloride in an agate mortar for 1 hour, place the ground mixture in a muffle furnace, and keep it at 1150 ° C for 15 hours. After taking it out, it is repeatedly filtered and washed with deionized water, and then the material is placed in a drying oven at 80 ° C overnight to obtain K, Al-SrTiO3 nanocatalyst material. Take 0.5 g of K, Al-SrTiO3 nanoparticles and disperse them in an aqueous solution, add 1.65 mg of NaRhCl6, 0.85 mg of Cr(NO3)2 and 1.04 mg of Co(NO3)3, and irradiate it with 300W xenon lamp for 1 hour, filter, wash and dry it to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0071] Secondly, 0.98g acrylamide monomer (AM), 14.7mg N, N'-methylenebisacrylamide and 10ml deionized water were mixed to obtain AM solution. Then, 1.05g polyvinyl alcohol (PVA) was dissolved in 10ml deionized water by heating and continuous stirring. 7ml PVA solution was added to the prepared AM solution, ultrasonicated in an ultrasonic bath for 15min, and then 0.0098g ammonium persulfate, 125μL glutaraldehyde and 40μL concentrated hydrochloric acid were added and ultrasonicated for 5min to obtain a mixed solution of AM and PVA. The solution was poured into an acrylic mold, and after degassing in a vacuum, it was placed in an oven at 50°C for pre-curing for 0.5h to obtain a sol-like PVA / PAM.

[0072] Finally, 5 mg RhCrO x / K,Al-SrTiO3 / CoOOH were dispersed in 2 ml of aqueous solution, dropped on the surface of sol-like PVA / PAM, then frozen with liquid nitrogen, put into a vacuum drying oven for curing at 80 °C for 3 h, frozen with liquid nitrogen again, put into a freeze dryer for freeze drying at -20 °C for 40 h, and K,Al-SrTiO3@PVA / PAM hydrogel was obtained.

[0073] The salt tolerance of the K and Al-SrTiO3@PVA / PAM hydrogels prepared in the above comparative examples reached 1.84 kg·m -2 ·h -1 , which is higher than that of Example 2, and its hydrogen evolution rate is 162.3mmol·m -2 ·h -1 , compared with 220.2mmol·m in Example 2 -2 ·h -1 Relatively low.

[0074] Comparative Example 3

[0075] A strontium titanate catalyst for solar seawater decomposition comprises the following steps:

[0076] First, weigh 0.008 mol of potassium carbonate, 0.008 mol of aluminum oxide and 1 g of SrTiO3, add 2 ml of ethanol, mix and grind in an agate mortar at room temperature for 1 hour, place the ground mixture in a muffle furnace, and keep it at 500 ° C for 10 hours. After taking it out, mix and grind it with 14 g of strontium chloride in an agate mortar for 1 hour, place the ground mixture in a muffle furnace, and keep it at 1150 ° C for 15 hours. After taking it out, it is repeatedly filtered and washed with deionized water, and then the material is placed in a drying oven at 80 ° C overnight to obtain K, Al-SrTiO3 nanocatalyst material. Take 0.5 g of K, Al-SrTiO3 nanoparticles and disperse them in an aqueous solution, add 1.65 mg of NaRhCl6, 0.85 mg of Cr(NO3)2 and 1.04 mg of Co(NO3)3, and irradiate it with 300W xenon lamp for 1 hour, filter, wash and dry it to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

[0077] like Figure 6 As shown in Figure 2, the hydrogen-oxygen ratio of K-Al-SrTiO3 in water decomposition performance is close to 2:1, and the hydrogen evolution rate reaches 79.62 mmol·m -2 ·h -1 The oxygen evolution rate reached 36.17mmol·m -2 ·h -1 Obviously, compared with the composite catalyst prepared in Example 2, the hydrogel composite catalyst has better catalytic activity. When the catalyst prepared in Comparative Example 3 was subjected to a salt resistance test, the mass change rate reached 2.67 kg·m -2 ·h -1 Much higher than the salt tolerance obtained in the examples

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen, characterized in that: The preparation method comprises the following steps: S1. Preparation of K and Al double metal ion co-doped SrTiO3 by solid phase grinding; S2, preparing PVA / PAM sol by chemical crosslinking method, including: mixing PVA solution with AM monomer solution, ultrasonicating in a cell disruptor for 15 minutes, adding an auxiliary agent, and curing for 0.5-1 hour to obtain PVA / PAM sol; S3. K and Al double metal ions are co-doped into SrTiO3 by liquid phase grafting method and loaded on the upper layer of PVA / PAM double-chain network three-dimensional porous hydrogel to obtain K, Al-SrTiO3 semiconductor composite hydrogel.

2. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen as claimed in claim 1, characterized in that: In S1, the method for preparing K and Al bimetallic ion co-doped SrTiO3 by solid phase grinding includes: mixing K salt and Al salt with SrTiO3, adding ethanol and fully wet grinding, drying, and performing a first heat treatment to obtain a precursor, and then grinding the precursor with strontium chloride and performing a second heat treatment to obtain K and Al bimetallic ion co-doped SrTiO3.

3. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen as claimed in claim 2, characterized in that: The first heat treatment temperature is 500℃ and the time is 10h.

4. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen as claimed in claim 2, characterized in that: The temperature of the second heat treatment is 900-1200°C and the time is 10-20h.

5. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen as claimed in claim 2, characterized in that: After the second heat treatment, the method further includes dissolving the sample and then filtering it to obtain K and Al bimetallic ion co-doped SrTiO3.

6. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen as claimed in claim 2, characterized in that: After obtaining K and Al double metal ion co-doped SrTiO3, the following step further comprises: mixing K and Al double metal ion co-doped SrTiO3 with NaRhCl6, Cr(NO3)2 and Co(NO3)3 to obtain RhCrO x / K,Al-SrTiO3 / CoOOH nanocomposite photocatalyst.

7. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen as claimed in claim 1, characterized in that: The PVA solution is an aqueous solution of polyvinyl alcohol, and the AM monomer solution is an aqueous solution containing acrylamide monomer and N,N'-methylenebisacrylamide; the auxiliary agent includes ammonium persulfate, glutaraldehyde and concentrated hydrochloric acid; and the curing temperature is 50°C.

8. The method for preparing a semiconductor composite hydrogel catalyst for photolysis of seawater for hydrogen production as claimed in claim 1, wherein in S3, the method for preparing K, Al-SrTiO3 semiconductor composite hydrogel comprises: The K and Al bimetallic ions co-doped SrTiO3 obtained in S1 are dispersed in water to obtain K, Al-SrTiO3 suspension, and the K, Al-SrTiO3 suspension is added dropwise to the PVA / PAM sol prepared in S2. After freezing treatment, it is solidified at 80°C for 1-5h, and then freeze-dried at -20°C for 24-60h to obtain K, Al-SrTiO3 semiconductor composite hydrogel.

9. A semiconductor composite hydrogel catalyst for photolysis of seawater to produce hydrogen, characterized in that: The preparation method is described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Modified CdS / ZnS quantum dots prepared by using sol-gel method and application of modified CdS / ZnS quantum dots in photocatalytic hydrogen evolution

    CN110003892A

  • Preparation method of semiconductor catalyst for hydrogen production and oxygen production through sunlight catalytic water decomposition

    CN114570385A